Effect of agave fiber surface treatment on the properties of polyethylene composites produced by dry‐blending and compression molding. Issue 1 (7th May 2015) - Cisneros‐López, E.O.; Anzaldo, J.; Fuentes‐Talavera, F.J.; González‐Núñez, R.; Robledo‐Ortíz, J.R.; Rodrigue, D.
Abstract : In this work, the effect of natural fiber surface treatment with maleated polyethylene (MAPE) is presented to improve the mechanical properties of natural fiber composites (NFC). In particular, a simple dry blending technique was used to disperse natural fibers (agave) in a polymer matrix (linear low density polyethylene) and produce samples via compression molding. The effect of fiber content was also studied (0, 10, 20, 30, and 40 wt%) and the samples were characterized in terms of morphology, density, hardness, as well as mechanical (tensile, flexion, and impact) and thermal (DSC and TGA) properties. The results show that the simple dry‐blending method is efficient to produce homogeneous NFC and that surface treatment can substantially improve composite modulus (164%) and strength (121%). POLYM. COMPOS., 38:96–104, 2017. © 2015 Society of Plastics Engineers